1999
DOI: 10.1128/jcm.37.3.734-741.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cholera in Vietnam: Changes in Genotypes and Emergence of Class I Integrons Containing Aminoglycoside Resistance Gene Cassettes in Vibrio cholerae O1 Strains Isolated from 1979 to 1996

Abstract: The number of cholera cases and the mortality rates reported from different regions of Vietnam varied considerably in the period from 1979 to 1996, with between 2,500 and 6,000 cases reported annually from 1992 to 1995. Annual mortality rates ranged from 2.0 to 9.6% from 1979 to 1983 to less than 1.8% after 1983. Major cholera outbreaks were reported from the High Plateau region for the first time in 1994 and 1995; this is an area with limited access to health services and safe drinking-water supplies. All cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 44 publications
5
49
0
1
Order By: Relevance
“…The perpetual phenomenon of lateral gene transfer (Jain et al, 1999) will inevitably lead to an encounter between a class 1 integron and a bacterial species harbouring a SI. This is supported by the recent finding of class 1 integrons in many V. cholerae isolates (Dalsgaard et al, 1999;2000a,b;Falbo et al, 1999) and a new fourth class of resistance integron in the SXT ET constin of V. cholerae (Hochhut et al, 2001). We have shown that class 1 integrons can randomly recruit the gene cassettes harboured within SIs.…”
Section: Discussionsupporting
confidence: 74%
“…The perpetual phenomenon of lateral gene transfer (Jain et al, 1999) will inevitably lead to an encounter between a class 1 integron and a bacterial species harbouring a SI. This is supported by the recent finding of class 1 integrons in many V. cholerae isolates (Dalsgaard et al, 1999;2000a,b;Falbo et al, 1999) and a new fourth class of resistance integron in the SXT ET constin of V. cholerae (Hochhut et al, 2001). We have shown that class 1 integrons can randomly recruit the gene cassettes harboured within SIs.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have described the presence of a class 1 integron in multiple strains or species [15], outbreaks caused by a single strain with an integron [17,29,33,59], multiple integrons [78,79], or a combination of these factors [8][9][10][11]18,19,21,32,55,58,80]. Remarkably, most of these reports come from Western Europe and Eastern Asia, but there are also reports from Africa [55,60,81] and South America [13,65,81].…”
Section: E P I D E M I O L O G Ymentioning
confidence: 99%
“…Vibrio cholerae O1 biotype El Tor came to South Vietnam in 1964 from Indonesia and was detected mainly in the central coastal areas and in South Vietnam. Besides the specific natural and socio economic factors, the long lasting war contributed to the epidemic explosion of the disease (Dalsgaard et al, 1997(Dalsgaard et al, , 1999. In recent years, prevention by vaccine campaigns (Vu et al, 2003) and environmental control as well as case treatment resulted in a significant control of cholera epidemics in Vietnam and a relative low drug resistance profile in V. cholerae, compared with other epidemics in other developing countries (Dalsgaard et al, 2001;Thungapathra et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the first half of the 1990s new multiple resistant strains of V. cholerae O1 emerged: these strains were characterized by streptomycin and spectinomycin resistances located on class 1 integrons (Dalsgaard et al, 1999). Aminoglycoside resistant integrons have also been found in Shigella spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation